2022
DOI: 10.1186/s12877-022-03066-8
|View full text |Cite
|
Sign up to set email alerts
|

Predictivity of the comorbidity indices for geriatric syndromes

Abstract: Background The aging population and increasing chronic diseases make a tremendous burden on the health care system. The study evaluated the relationship between comorbidity indices and common geriatric syndromes. Methods A total of 366 patients who were hospitalized in a university geriatric inpatient service were included in the study. Sociodemographic characteristics, laboratory findings, and comprehensive geriatric assessment(CGA) parameters wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 43 publications
(51 reference statements)
1
18
0
Order By: Relevance
“…Nevertheless, this data are consistent with the literature (29-31). Regarding the correlations between the variables, as expected (28), CIRS Tot., CIRS ICC, and CIRS ISC were mutually very strongly correlated with each other-since a single index is insufficient (32), we also summarized the principal comorbidities-, and also the strong relationship between ADL, IADL, and POMA is consistent with the literature (14,33). It is interesting to underline that MNA is the most correlated variable with > 0.4: it is correlated with GDS, ADL, IADL, and POMA.…”
Section: Discussionsupporting
confidence: 79%
“…Nevertheless, this data are consistent with the literature (29-31). Regarding the correlations between the variables, as expected (28), CIRS Tot., CIRS ICC, and CIRS ISC were mutually very strongly correlated with each other-since a single index is insufficient (32), we also summarized the principal comorbidities-, and also the strong relationship between ADL, IADL, and POMA is consistent with the literature (14,33). It is interesting to underline that MNA is the most correlated variable with > 0.4: it is correlated with GDS, ADL, IADL, and POMA.…”
Section: Discussionsupporting
confidence: 79%
“…Multimorbidity was often accompanied with frailty, polypharmacy, and dementia. 28 , 29 Hung et al 30 found that the comprehensive geriatric assessment guided multidisciplinary interventions (including physical therapy, psychotherapy, pharmacist education, and social resources linkage) were effective to improve frail severity, physical function, and depressive and nutritional status in elderly (45% with dementia). Appropriate intervention toward frail status and polypharmacy maybe also a solution to deal with this complex population.…”
Section: Discussionmentioning
confidence: 99%
“…9 Although these multimorbidity indices are both associated with elements of comprehensive geriatric assessment such as frailty, dementia, polypharmacy, or malnutrition, key elements such as sensory deficits, functional independence or mobility problems, and nutritional deficiency may not be sufficiently captured. 39 Previous reviews have shown that proxy scores based on electronic health records perform similarly to many vali- dated clinical tools. 10,16 Although there is a strong case for preferring the frailty and multidomain assessment framework for risk stratification of older patients in acute care over multimorbidity, 40,41 these 2 approaches are possibly complementary.…”
Section: Discussionmentioning
confidence: 99%